Proftability of the edible mushroom Suillus luteus exploitation for timber producers and for rural families in the Andean region of Chubut province, Argentina - Fernández, María Victoria; Barroetaveña, Carolina; Bassani, Vilma; Ríos, Fernanda (Bosque (Valdivia), 2017)
Since mid last century, approximately 22,700 ha of Pinus spp. have been planted in the Andean region of Chubut, Argentina. Along with these tree species, the edible mushroom Suillus luteus (slippery jack) also proliferates, with a mean dry productivity of 35 kg ha-1 year-1 for this region. The economic exploitation of this product is currently carried out informally, becoming this non-wood forest product a source of additional revenues for low-income families, but it is unknown so far the returns that its exploitation can bring to forest producers, in addition to timber production. Therefore, two objectives were set for this study: to assess the potential of the edible mushrooms S. luteus to improve the profitability of forest producers, and to evaluate the contribution that the collection and sale of this product may represent to the income of rural households. To do this, the revenues and costs associated with tree harvesting and mushrooms drying were incorporated in the cash flow of forest management, estimating the corresponding performance indicators. On the other hand, socio-economic indicators of contributions to family incomes that the informal exploitation of this resource could provide were calculated. Results indicate that it is possible to improve forest producer profitability by selling dry S. luteus only in those plantations with high productivity, as the internal rate of return increases between 5 to 8 %. Rural families would receive more pay per hour worked selling fresh mushrooms, but the total income would be higher selling it dry.